Evaluation of Post-Claim Verification Implementation for National Health Insurance Outpatient Services in 2024: Evaluasi Pelaksanaan Verifikasi Pasca Klaim untuk Layanan Jaminan Kesehatan Nasional Rawat Jalan Tahun 2024 - Setiyawan, Hery; Widowati, Vidya; Darsono, Darsono; Saputri, Ratna Aprilia (Universitas Muhammadiyah Sidoarjo, 2025)
One of the challenges in the implementation of JKN (National Health Insurance) in health care facilities is the possibility of fraud. So in an effort to prevent fraud and ensure the quality of claims BPJS made a new policy for the implementation of postclaim verification after the claim is paid. So if there is a discrepancy in the nominal claim, the hospital has the right to refund the difference to the BPJS. This study is a descriptive qualitative research using a case study approach. The subjects were outpatient coder, internal verifier, and head of pusjamkes as source triangulation. The purpose of this study was to determine the implementation of postclaim verification of outpatient JKN at RSU PKU Muhammadiyah Bantul in 2024. The results of this study are (1)the flow of settlement implementation is appropriate; (2)the percentage of 403 postclaim verification data of outpatient JKN, (65%) verified data and (35%) clarified data. The data are clarified based on each aspect, coding aspects (58%), administrative aspects(23%), and medical aspects(19%); (3)the factors that cause Postclaim verification data clarified outpatient JKN is due to high workload, lack of human resources, incompleteness and inaccuracy of service documentation, does not have SPO(standard operating procedure); (4) efforts to resolve by submitting the number of human resources, confirmation with related PPA (Professional Caregiver), conducting evaluation and monitoring, and implementation of the settlement refers to the BA(official report) agreement, PNPK, and hospital PPK. The conclusion of this study is that the coding aspect is the highest aspect of the postclaim verification data clarified outpatient JKN, the factors that cause the elements of man(human), material(material),and method(method).